Penggunaan Obat Off-Label dan Unlicensed pada Bayi dan Neonatus di Bangsal Anak - Zakky Cholisoh; Siti Alfiatur Rohmah (Universitas Muhammadiyah Surakarta, 2020)
The prescription of medications outside the listed marketing authorizations (MA) is considered off-label. This practice is still frequently occurs in clinical practice. One of the reasons is because the lack of clinical trials and research in babies and neonates. This study was conducted to evaluate the off-label and unlicensed medications, their level of use and further describe the level of evidence of the commonly prescribed off-label and unlicensed medication in this population. Medications prescription and administration to hospitalised babies and neonates were recorded. Medication record data in a year were collected. Medication- licensing status of all drugs administered was determined according to marketing authorization information from monograph. The data then were categorised as off-label and unlicensed if the indication, dosage regimens, age category, and route of administration were not listed in the market authorization of the products. Furthermore the administrations of the most commonly used off-label medications were reviewed based on published journal articles to determine their level of evidence. Total medications administered during a year were 2,576 which were obtained from 139 patients. Of all, 15.25% (339) and 2.69% (69) medications administered were categorised as off-label and unlicensed respectively. Off-label of dosage regimens and route of administration were not identified, but 1.63% (42) medications were used for indications that were not listed in the (MA), and 13,63% (351) were prescribed out of age category of the listed marketing authorization. Off-label drug that often prescribed are salbutamol which had no evidence to support its use; valproic acid which had high level of evidence against its use on baby and neonates; and ondancetron which had high level of evidence to be used outside its marketing authorization.